Etyczne problemy sprawowania władzy w zarządzaniu przedsiębiorstwem - Pawlak, Zbigniew; Smoleń, Andrzej (Annales. Etyka w Życiu Gospodarczym, 2008)
When power is exercised in the enterprise some ethical issues might occur with businessownership, personnel policy, working conditions etc.These issues and ways of addressing them were depicted and interpreted from the perspective ofthe Church’s social teachings included in papal encyclicals, viz.: Rerum novarum, Laborem exercens,Centesimus Annus.In the Church’s social teachings a number of principles were noticed that are favourable forthe ethical corporate management including the principle of the primacy of work over capital, right toprivate ownership, right to establish professional associations, right to fair pay, right to fulfil religiousobligations and having rest during holidays, a duty to support the weak and the needy (solidarityprinciple).The analysis of the social content of papal encyclicals showed two faces of power. On the onehand it is necessary and has positive effects (introduction of corporate governance, taking rightdecisions, prevention of theft and assets devastation etc.); on the other hand improper power exercisemay lead to a number of undesirable effects (corruption, worker discrimination, thriftlessness etc.)The paper identifies also sources, forms and power exercising planes in the enterprise.